2022
DOI: 10.22271/tpi.2022.v11.i9w.15658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different spacing on varieties of Brinjal (Solanum melongena L.)

Abstract: The present investigation entitled "Effect of different spacing on varieties of brinjal (Solanum melongena L.)'' was carried out during Late Kharif season of 2020-21 at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The higher inter-cluster distance indicated greater genetic divergence between the genotypes of these clusters while lower inter cluster values between the clusters suggested that the genotypes of the clusters were not much genetically diverse from each other Das and Das [12] studied the genetic divergence in brinjal and grouped 26 genotypes into 11 clusters and also reported maximum and minimum inter and intra cluster distances". [13] A perusal of Table 3 total fruit yield per plant showed the highest contribution (41.10%) followed by total phenol content (20.93%), ascorbic acid (10.89%), non-reducing sugar (10.19%), reducing sugars (4.94%), average fruit weight (4.50%), total sugars (2.21%), number of primary branch per plant (1.36%), days to 50% flowering (1.24%), plant height (0.96%), T.S.S (0.67%), days to first fruit harvest (0.45%), fruit circumference (0.28%), number of fruits per plant (0.15%) and fruit polar length (0.14%)for total divergence among the available genotypes of egg plant. Such contribution towards the genetic divergence has been also reported by Das and Das [8].…”
Section: Resultsmentioning
confidence: 99%
“…The higher inter-cluster distance indicated greater genetic divergence between the genotypes of these clusters while lower inter cluster values between the clusters suggested that the genotypes of the clusters were not much genetically diverse from each other Das and Das [12] studied the genetic divergence in brinjal and grouped 26 genotypes into 11 clusters and also reported maximum and minimum inter and intra cluster distances". [13] A perusal of Table 3 total fruit yield per plant showed the highest contribution (41.10%) followed by total phenol content (20.93%), ascorbic acid (10.89%), non-reducing sugar (10.19%), reducing sugars (4.94%), average fruit weight (4.50%), total sugars (2.21%), number of primary branch per plant (1.36%), days to 50% flowering (1.24%), plant height (0.96%), T.S.S (0.67%), days to first fruit harvest (0.45%), fruit circumference (0.28%), number of fruits per plant (0.15%) and fruit polar length (0.14%)for total divergence among the available genotypes of egg plant. Such contribution towards the genetic divergence has been also reported by Das and Das [8].…”
Section: Resultsmentioning
confidence: 99%